CYP1A1 and GSTM1 genes associated with the risk of developing colorectal cancer: a case-control study in the Lima region of Peru - Alvarado, Angel T. (2025)
The presence of CYP1A1 allelic variants and deletion of the glutathione S-transferase GSTM1 gene, and their imbalance, have been suggested as risk factors for inducing colorectal cancer (CRCa). The objective was to identify CYP1A1 and GSTM1 and evaluate the association with the risk of developing colorectal cancer in a sample of cases and controls from Lima, Peru. This was a case-control study of CYP1A1 and GSTM1 genes in 50 samples from patients diagnosed with colorectal cancer and 50 samples from controls without cancer, using the PCR-based restriction fragment length polymorphism method. A significant risk of developing CRCa was found in the following groups: GSTM1*0 carriers with no history of smoking or family history of cancer (OR = 3.56, 95% CI 1.43–8.88, p = 0.0060); GSTM1*0 with family history of cancer without smoking (OR = 2.81, 95% CI 0.35–22.49, p = 0.3280); GSTM1*0 exacerbated by smoking (OR = 1.41, 95% CI 0.11–17.11, p = 0.7880); CYP1A1*2A/*2A carriers with family history and smoking (OR = 1.50, 95% CI 0.13–16.54, p = 0.7410). An association of wild genotypes exacerbated by non-genetic factors with risk of developing CRCa was also found: CYP1A1*1A/*1A with family history of cancer but no history of smoking (OR = 2.94, 95% CI 0.11–35.80, p = 0.6380); GSTM1 (+) with history of smoking but no family history of cancer (OR = 5.63, 95% CI 0.46–68.46, p = 0.1750); GSTM1 (+) associated with family history and smoking (OR = 9.86, 95% CI 1.77–54.89, p = 0.0090). According to univariate statistical analysis, carriers of CYP1A1*2A and GSTM1*0 without association with family history of cancer and smoking would not be related to the risk of CRCa. An association was established between GSTM1*0 and CYPA1*2A/*2A with colorectal cancer exacerbated by family history and smoking. The risk is higher with wild-type genotypes of CYP1A1*1A/*1A and GSTM1 (+) induced by family history and smoking, respectively.